Electron and light hyperbolicity correlation in α-CaGe_{2} - Han Gao; Xuejin Zhang; Chao Ding; Mingzheng Wang; Juan Wang; Bo Yang; Mingwen Zhao (Physical Review Research)
Hyperbolic materials, characterized by their hyperbolic dispersion relations of waves, have attracted significant attention due to their distinct equifrequency contours. This study establishes a correlation between electron hyperbolicity and light hyperbolicity, unveiling fascinating scenarios resulting from their interplay. The transition of electron hyperbolicity from type-I to type-II, induced by varying the chemical potential of electrons, also triggers a similar transition in light hyperbolicity. Through first-principles calculations, α-CaGe_{2} is identified as a promising material for achieving this transition. The tunable optical responses in α-CaGe_{2} under different doping conditions allow for the creation of heterostructures, resulting in the emergence of unique optical phenomena such as negative refraction and negative reflection. The distinctive electronic states proposed in this study not only pave the way for further exploration of hyperbolic materials but also lay the groundwork for designing innovative optoelectronic devices that expand the functional possibilities of these intriguing materials.